An Estimation of the Impact of Uninterpretable Power Supply Systems on Electricity Distribution Utility of Pakistan - Usama Qazi,; Muhammad Rizwan Ali ,; Abdul Moqueet, (Journal of Basic & Applied Sciences, 2018)
The power crisis in Pakistan is getting worse day by day. Electricity shortfall has reached upto 5000 MW. Due to power shortage consumers are facing load shedding for more than 6 hrs a day. To get rid of this crisis consumers have opted fossil fueled generators and UPS. Due to excessive availability UPS are more popular than generators. Although, UPS satisfy the need of consumers during power outage hour but due to efficiency constrains these UPS put extra burden on grid. This study estimates the power loss that occurs in consequence of using inefficient UPS. It has been found that about 3.75% of total power provided by the utility is lost during charging and discharging. The research also provides suggestions to eradicate the efficiency losses which occurred as a result of using UPS.